ESENSI AKUNTANSI SYARIAH DI LEMBAGA KEUANGAN SYARIAH DI INDONESIA - Ilman Huda, Moh Afthon; Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Sharia financial institutions in Indonesia are growing rapidly in line with increasing public awareness of the importance of financial management in accordance with sharia principles. Sharia accounting is very important in sharia financial institutions, because sharia accounting plays an important role in maintaining compliance with sharia principles and ensuring that financial transactions are carried out in accordance with sharia principles. The essence of sharia accounting in sharia financial institutions in Indonesia includes sharia principles, Avoid riba, gharar, maysir and muamalah which are haram in every financial transaction. Apart from that, sharia accounting must follow sharia accounting standards set by the Indonesian Accountants Association (IAI). Several things that need to be considered in implementing sharia accounting in sharia financial institutions in Indonesia are the use of information systems, implementation of PSAK, supervision and employee training.